2023
DOI: 10.1021/acs.jpcb.2c07371
|View full text |Cite
|
Sign up to set email alerts
|

Local Hydration Control and Functional Implications Through S-Nitrosylation of Proteins: Kirsten Rat Sarcoma Virus (K-RAS) and Hemoglobin (Hb)

Abstract: S-nitrosylation, the covalent addition of NO to the thiol side chain of cysteine, is an important post-transitional modification (PTM) that can affect the function of proteins. As such, PTMs extend and diversify protein function and thus characterizing consequences of PTM at a molecular level is of great interest. Although PTMs can be detected through various direct/indirect methods, they lack the capability to investigate the modifications with molecular detail. In the present work local and global structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…As H 2 is not able to directly facilitate post-translational modifications (PTMs) of proteins such as S-nitrosylation, there must be a different interaction involved. Rather than PTMs affecting directly polypeptide topology, very recent work on the hydration of proteins such as hemoglobin suggests that the interaction with water may affect the allosteric nature of the polypeptides, and hence their function [102]. It is possible that inert gases such as Xe (or H 2 ) may have an influence on such hydration by occupying polypeptide cavities.…”
Section: Discussionmentioning
confidence: 99%
“…As H 2 is not able to directly facilitate post-translational modifications (PTMs) of proteins such as S-nitrosylation, there must be a different interaction involved. Rather than PTMs affecting directly polypeptide topology, very recent work on the hydration of proteins such as hemoglobin suggests that the interaction with water may affect the allosteric nature of the polypeptides, and hence their function [102]. It is possible that inert gases such as Xe (or H 2 ) may have an influence on such hydration by occupying polypeptide cavities.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, by means of sophisticated computational simulations, it was found that S-nitrosylation of K-Ras affects the dynamics of this protein, specifically at the structural level [ 56 ]. These authors demonstrated that S-nitrosylation of K-Ras on Cys118 residue alters the flexibility of the protein leading to a hardening of the Switch I region.…”
Section: S-nitrosylation Of Ras Enhances Guanine Nucleotide Exchangementioning
confidence: 99%
“…These authors demonstrated that S-nitrosylation of K-Ras on Cys118 residue alters the flexibility of the protein leading to a hardening of the Switch I region. This is the region in the structure of the protein where interactions with GAPs and effector molecules occur, meaning that changes in this area have functional implications [ 56 ].…”
Section: S-nitrosylation Of Ras Enhances Guanine Nucleotide Exchangementioning
confidence: 99%